Tahlil Kitab Ta’lim Al-Lughah Al-‘Arabiyyah Al-Ladziy Allafahu Al-Duktur Hidayat - M. Kamil Ramma Oensyar; Nur Amalia (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2021)
Textbooks are a very important component in the learning process. The researcher conducts an analysis here using the theory of Rusydi Ahmad Thu'aimah in his book Manahij Tadris Al-lughah Al-Arabiyyah Bi-ta'lim Al-asasi about the criteria for writing Arabic books for elementary third graders. The results of the study explain that: Dars (1) regarding "Ta'aruf" is all appropriate except for maharah istima'. Dars (2) regarding “Al-Amiluna Bil-Madrasah” are all appropriate except maharah istima' and qira'ah. Dars (3) on “Al-marafiq Wal-Adawatul Madrasiyyah” are all appropriate except for istima' maharah. Dars (4) on “Al-alwan” are all appropriate except maharah istima'. Dars (5) on “Al-unwan” are all appropriate except maharah istima' and qira'ah. Dars (6) on “Baiti” are all appropriate except maharah istima'. Dars (7) on “Min Yaumiyyatunal Usroh” are all in agreement except maharah istima' and qira'ah.الكتب المدرسية هي عنصر مهم للغاية في عملية التعليم. أجرى الباحث تحليلاً هنا باستخدام نظرية الرشدي أحمد طعيمة في كتابه "مناهج تدريس اللغة العربية بالتعليم الأساسي" حول معايير تأليف الكتب العربية لطلاب الصف الثالث الابتدائي. وقد أوضحت نتائج الدراسة أن: دارس (1) بخصوص "التعارف" مناسبة كلها باستثناء مهارة الاستماع (2) بخصوص "العاملون بالمدرسة" كلها مناسبة باستثناء مهارة الاستماع والقراءة (3) في "المرافق والضوئية" كلها مناسبة باستثناء مهارة الاستماع. (4) وفي "الألوان" كلها مناسبة باستثناء مهارة الاستماع. (5) وفي "العنوان" كلها مناسبة ما عدا مهارة الاستماع والقراءة. (6) وفي "بيتي" كلها مناسبة باستثناء مهارة الاستماع. (7) وفي "من يوميات الأسرة" جميعهم متفقون فيما عدا مهارة الاستماع والقراءة.